A Renormalization Approach to the blowup structure in Shell Models for MHD Turbulence (Physicae Organum - Revista dos Estudantes de Física da UnB, 2015)
We study blowup (formation of finite-time singularity) in a shell model for magnetohydrodynamic (MHD) turbulence, showing blowup for this model and proving a criterion for it's occurance. We introduce a renormalization scheme which takes blowup time to infinity and study some basic properties of the renormalized model while proving it's consistency. Relation between the renormalized and original models is studied and we propose a method of analysis for a special solution of the renormalized model. Some numeric solutions of the models are shown.